GGE biplot analysis of genotype by environment interaction of barley cultivars - Güngör, Hüseyin; Fatih Çakır, Mehmet; Dumlupınar, Ziya (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
This study was conducted out to determine grain yield, yield components, and some quality charecteristics of 17 barley (Hordeum vulgare L.) genotypes at six environments in Thrace region of Turkey, using principal component analysis (PCA) and genotype (G) + genotype × environment interaction (GGE) biplot analysis to define the genotypes with higher yield and desirable quality traits during the 2016-2017 and 2017-2018 cropping seasons. Mean values of the genotypes varied from 5106-6753 kg.ha-1 for grain yield, 103.4-117.1 days for heading date, 94.6-110.3 cm for plant height, 6.26-10.07 cm for spike length, 25.0-75.5 number of grains per spike, 1.20-2.99 g grain weight per spike, 35.0-50.5 g for thousand kernel and weight, 56.4-64.1 kg.hl-1 for test weight. The relationships among the examined traits and genotypes was 53.9 % as defined by PC biplot analyses. GGE biplot analysis represented 94.77 % of the relationship of G + GE for grain yield. Two mega circles were formed according to grain yield, Zeus genotype for E1, E2 and E5 locations and Arcanda genotype for E3, E4 and E6 locations were determined as prominent genotypes. Zeus and Arcanda cultivars have been identified as the most ideal and stable genotypes.